Additive manufacturing in biomedical sciences and the need for definitions and norms. (September 2015) - Chhaya, Mohit P; Poh, Patrina SP; Balmayor, Elizabeth R; van Griensven, Martijn; Schantz, Jan-Thorsten; Hutmacher, Dietmar W
<x xml:space="preserve">Abstract</x> The application of additive biomanufacturing represents one of the most rapidly advancing areas of biomedical science, in which engineers, scientists, and clinicians are contributing to the future of health care. The combined efforts of a large number of groups around the globe have developed a strong research thrust that has resulted in a large number of publications. Reviewing this body of literature, there is an increasing trend of research groups inventing their own definitions and terminology. This has made it difficult to find and compare the results. Therefore, to move the field constructively forward, it is a conditio sine qua non to clarify various terminologies and standards. Based on this background, this article advocates tightening the terminology and has the objective of penning out definitions that will ultimately allow the development of official industry standard terms, such as American Society for Testing and Materials and or International Organization for Standardization for technologies developed for Tissue Engineering and Regenerative Medicine.